2022
DOI: 10.1155/2022/7123416
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Seepage of Chemical Grout Flow in Rock Fracture under Temperature Field

Abstract: Grouting technology is widely used to improve the mechanical properties and reduce the permeability of the rock in underground engineering. Fluidity is important to promote the grout to be injected into longer fractures, so chemical grouts with low viscosity and adjustable gel time are usually chosen to increase this property. However, the high temperature in some deep engineering leads to a faster hydration rate of the chemical grout than that in the room temperature environment, resulting in the decrease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Compared with the results from other researches [40][41][42], the pile-soil stress radio at stable stage in this project is still relatively small, so improved methods could be applied to further increase pile-soil stress radio. Researches have shown that the stiffened cushion can transfer the upper load to the pile top, resulting in the rise of pile-soil stress ratio, thus improving the bearing capacity of the foundation.…”
Section: Analysis Of Pile-soil Stressmentioning
confidence: 74%
“…Compared with the results from other researches [40][41][42], the pile-soil stress radio at stable stage in this project is still relatively small, so improved methods could be applied to further increase pile-soil stress radio. Researches have shown that the stiffened cushion can transfer the upper load to the pile top, resulting in the rise of pile-soil stress ratio, thus improving the bearing capacity of the foundation.…”
Section: Analysis Of Pile-soil Stressmentioning
confidence: 74%